2021
DOI: 10.21203/rs.3.rs-1106929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Surgery Admissions and The COVID-19 Pandemic: Did The First Wave Really Change Our Practice? Results of An ACOI/WSES International Audit On 6263 Patients.

Abstract: IntroductionThe COVID-19 pandemic is having a deep impact on emergency surgical services, with a significant reduction of patients admitted into emergency surgical units world widely. Reliable figures of this reduction have not been produced yet. Our international audit aimed at giving a precise snapshot of the absolute and relative changes of emergency surgical admissions at the outbreak of the pandemic. Materials and methodsDatasets of patients admitted as general surgical emergencies into 45 internationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, a significant difference has been found for both weekdays and weekends in the rate of frail versus non-frail patients admitted into the participating surgical units during the COVID first wave versus non-COVID period, with more frail patients admitted during the COVID period (2020). This finding has already been highlighted and discussed in another paper [2]. Interestingly, the modalities of treatment changed significantly during the weekend, probably due to local availability or reduced adherence to guidance and protocols.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, a significant difference has been found for both weekdays and weekends in the rate of frail versus non-frail patients admitted into the participating surgical units during the COVID first wave versus non-COVID period, with more frail patients admitted during the COVID period (2020). This finding has already been highlighted and discussed in another paper [2]. Interestingly, the modalities of treatment changed significantly during the weekend, probably due to local availability or reduced adherence to guidance and protocols.…”
Section: Discussionmentioning
confidence: 54%
“…Data for this study were derived from the CovidICE-International Study database, whose characteristics have been reported elsewhere [2].…”
Section: Methodsmentioning
confidence: 99%
“…Overall, our findings show an absolute decrease in operative volume related to diverticulitis, yet an increase in emergency operations, cases involving an abscess and/or perforation, and rates of SIRS and septic shock during the pandemic. Many single-institution studies showed similar findings 3,7,8,[12][13][14] and have attributed this to a myriad of factors. Cirocchi et al 9 suggested that general operative volume decreased due to the employment of more conservative medical treatments for diverticulitis in lieu of inpatient or operative management, such as oral antibiotics and percutaneous drainage.…”
Section: Discussionmentioning
confidence: 67%
“…Acute cholecystitis and, more generally, biliary emergencies, represent about 20% of all the emergency surgical admissions [3]. For acute cholecystitis, current guidelines suggest an emergency cholecystectomy as first choice of treatment, to be performed ideally during the same index admission and by the laparoscopic approach [4].…”
Section: Discussionmentioning
confidence: 99%
“…Complications of gallstones represent about 20% of all the emergency surgical admissions [3]. Current recommendations are to perform a laparoscopic cholecystectomy (LC) during the acutely symptomatic phase of the index emergency admission due "hot gallbladder" (i.e., intractable biliary colic, acute cholecystitis, gallstones pancreatitis or jaundice due to biliary stones), in order to prevent recurrent symptoms and further complications, and reduce emergency department admissions, length of hospital stay and hospital costs [4].…”
Section: Introductionmentioning
confidence: 99%